Zakat Fund Management through Financial Technology in the Digital Era: A Maqāṣid al-Sharī‘ah Approach - Noviani, Tri Anisa; Khoiruddin; Sofiana, Anis (Al-Risalah, 2025)
This study examines the management of zakat funds through financial technology (fintech) in Indonesia's digital era from the perspective of maqāṣid syarī'ah, revealing critical gaps in Islamic finance literature. Although previous studies have explored the technical and managerial aspects of digital zakat, few have systematically disseminated fintech zakat platforms through the perspective of comprehensive maqāṣid syarī'ah principles. This study contributes by developing a maqāṣid evaluation framework specifically applied to digital zakat management, moving beyond normative discussions toward practical implementation analysis. Using a normative juridical method with descriptive-qualitative analysis, this study examines Law No. 23 of 2011 concerning Zakat Management, the DSN-MUI fatwa, and three main platforms: BAZNAS Digital, KitaBisa, and Dompet Dhuafa. Data analysis uses maqāṣid criteria mapping covering five dimensions: ḥifẓ al-dīn, ḥifẓ al-nafs, ḥifẓ al-'aql, ḥifẓ al-nasl, and ḥifẓ al-māl. The findings show that Indonesian digital zakat platforms have successfully integrated sharia principles with technological innovation, achieving 150% growth in transactions and a 40% increase in operational efficiency. However, critical challenges include a lack of digital literacy (which affects 35% of potential users), the risk of a decline in spiritual essence, and the absence of national standardization. New contributions from this research include.